The judicialisation of politics in India: origins and consequences of the power of the Indian supreme court - Fischer, Alexander (Universitätsbibliothek Heidelberg, 2020)
This thesis is a longitudinal study of judicial power in India and captures the history of the Supreme Court from the perspective of positive political theory. Combining measurements of competitiveness of political participation with quantitative indicators that describe the court as a composite actor, the thesis identifies both the structuration of opportunities for judicial power expansion as well as critical junctures resulting from the court’s strategic choices. Each chapter combines empirical data and historiographic narratives to portray such phases of institutional flux, re-conceptualizing the overall trend towards judicial power expansion as distinct sequences of judicial overreach, jurisdiction stripping, and judicial self-empowerment alternating between regime supportive judicial activism and judicial assertiveness. Like all good dependent variables the power of the Indian Supreme Court thus varies over time, while the theoretical frameworks for tying together this thesis always derive from the same paradigm of separation-of-power-games, drawing on strategic approaches in judicialization studies to explain juristocratic patterns of judicial power expansion in India.
Keywords: Hochschulschrift; Rechtsprechende Gewalt; Normenkontrolle